Pengaruh Pengetahuan dan Religiusitas terhadap Niat Usaha Mikro dan Kecil Penerima Program Sertifikasi Halal Gratis (SEHATI) 2025 di Jawa Barat - Sabila Syifa Noorazlina; Abdulah Safe’i; Evi Sopiah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This research is motivated by the low participation rate of micro and small enterprises (MSEs) in the free halal certification program (SEHATI) organized by the Halal Product Guarantee Agency (BPJPH), even though the program has been designed with easy procedures and no fees. This condition indicates a gap between facilitative policies and the internal readiness of business actors, especially regarding the aspects of knowledge and religiosity. Therefore, this study aims to analyze the influence of knowledge and religiosity on the intention of MSEs to participate in the SEHATI 2025 Program. This study uses a quantitative approach with a survey method of 124 MSMEs. Data were analyzed using multiple linear regression through the SPSS program version 27. The results show that knowledge has a positive and significant influence on the intention of MSEs, which indicates the importance of understanding the halal concept, certification procedures, and applicable regulatory provisions. Religiosity is also proven to have a positive and significant influence as a moral driving factor in running a business in accordance with halal principles. Together, knowledge and religiosity are able to explain 65.3% of the variation in the intention of MSMEs to participate in the halal certification program. These findings emphasize the need for integration between engineering education and strengthening religious values to increase MSEs participation in halal certification programs.